Checkpoint inhibitor‐based salvage regimens prior to autologous stem cell transplant improve event‐free survival in relapsed/refractory classic Hodgkin lymphoma. Issue 3 (11th January 2023) - Desai, Sanjal H.; Spinner, Michael A.; David, Kevin; Bachanova, Veronika; Goyal, Gaurav; Kahl, Brad; Dorritie, Kathleen; Azzi, Jacques; Kenkre, Vaishalee P.; Arai, Sally; Chang, Cheryl; Fusco, Brendon; et al.
Abstract: Clinical trials of novel salvage therapies have encouraging outcomes for relapsed/refractory transplant‐eligible classic Hodgkin lymphoma (R/R cHL) but comparison with conventional chemotherapy is lacking. Herein, we report the final analysis of a multicenter retrospective cohort of R/R cHL assessing outcomes by type of salvage therapy before autologous stem cell transplant (ASCT). R/R cHL patients who underwent ASCT at 14 institutions across the United States were included. Outcomes were compared among patients receiving conventional chemotherapy, brentuximab vedotin (BV) + chemotherapy, BV alone, and a checkpoint inhibitor (CPI)‐based regimens before ASCT. Study endpoints included event‐free survival (EFS), progression‐free survival (PFS), and overall survival (OS). All endpoints are defined from relapse. Of 936 patients, 728 received conventional chemotherapy, 73 received BV + chemotherapy, 70 received BV alone, and 65 received CPI‐based regimens prior to ASCT. When adjusted for time to relapse, pre‐ASCT response and use of BV maintenance, patients receiving CPI‐based regimens had superior 2‐year EFS compared to conventional chemotherapy, BV + chemotherapy, and BV alone (79.7, 49.6, 62.3, and 36.9%, respectively, p  < .0001). Among 649 patients transplanted after 1 line of salvage therapy, CPI‐based regimens were associated with superior 2‐year PFS compared to conventional chemotherapy (98% vs. 68.8%, hazard ratio: 0.1, 95% confidence interval: 0.03–0.5, p  < .0001). OS did not differ by pre‐ASCT salvage regimen. In this large multicenter retrospective study, CPI‐based regimens improved EFS and PFS compared to other salvage regimens independent of pre‐ASCT response. These data support earlier sequencing of CPI‐based regimens in R/R cHL in the pre‐ASCT setting.